2019
DOI: 10.3390/electronics8121541
|View full text |Cite
|
Sign up to set email alerts
|

A Wireless Sensors Network for Monitoring the Carasau Bread Manufacturing Process

Abstract: This work copes with the design and implementation of a wireless sensors network architecture to automatically and continuously monitor, for the first time, the manufacturing process of Sardinian Carasau bread. The case of a traditional bakery company facing the challenge of the Food-Industry 4.0 competitiveness is investigated. The process was analyzed to identify the most relevant variables to be monitored during the product manufacturing. Then, a heterogeneous, multi-tier wireless sensors network was design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 51 publications
1
50
0
Order By: Relevance
“…Likewise, it was also observed that the lowest values are reached in the third quarter of the year and that the highest values occur in the second and fourth quarters of the year. These results are in agreement with the general comments made in [ 28 ] about the CO concentration in Quito.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Likewise, it was also observed that the lowest values are reached in the third quarter of the year and that the highest values occur in the second and fourth quarters of the year. These results are in agreement with the general comments made in [ 28 ] about the CO concentration in Quito.…”
Section: Discussionsupporting
confidence: 93%
“…With the purpose of conducting the above-mentioned study, nonparametric tests such as the Kruskal-Wallis test and the Mann-Whitney U test [ 20 , 21 ] were used [ 19 ]. Other examples of recent publications in which nonparametric tests have been used to analyze measurements of air pollution variables can be found in [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonparametric statistical inference tools have also been used in the analysis of air pollution variables [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. This has been important, because if the data do not follow parametric distributions, then classical statistical inference is unfounded, which is the case of study in this research.…”
Section: Discussionmentioning
confidence: 99%
“…This has been important, because if the data do not follow parametric distributions, then classical statistical inference is unfounded, which is the case of study in this research. In this sense, in [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] nonparametric analysis tools have been used to study several variables of air pollution. Nevertheless, nonparametric analysis is much more sensitive to the influence of extreme values than robust analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation